Pengaruh Machiavelli, Kemudahan Pengisian SPT pada Kepatuhan WPOP dengan Penyuluhan Sebagai Pemoderasi - Alifia, Ratna; Noviari, Naniek (E-Jurnal Akuntansi; Vol 12 No 2 (2015), 2015)
This research purpose to testing effect of Machiavelli and easiness of complete SPT to compliance of individual taxpayers and testing of effect tax extension as moderating of Machiavelli and easiness of complete SPT relationship with tax compliance. This research was conducted in KPP Pratama South Badung using questionnaire technique. This research used 100 respondents with accidental sampling method. The analysis technique used Moderated Regression Analysis. The results shows Machiavelli negatively effect to compliance of individual taxpayers and easiness of complete SPT positive effec t to compliance of individual taxpayers. Effect of Machiavelli to compliance of individual taxpayers also moderated with negative directions by tax extension and effect easiness of complete SPT to compliance of individual taxpayers moderated with positive directions by tax extension.
Keywords: level of compliance individual taxpayers, machiavelli, easiness of complete SPT, tax extension